Immunotherapeutic Advancements for Glioblastoma - Ampie, Leonel; Woolf, Eric C.; Dardis, Christopher (Frontiers in Oncology, 2015)
Immunotherapy seeks to improve the body’s immune response to a tumor. Currently, the principal mechanisms employed are: 1) to improve an aspect of the immune response (e.g. T cell activation) and 2) to encourage the targeting of particular antigens. The latter is typically achieved by exposing the immune system to the antigen in question, in vivo, or in vitro followed by re-introduction of the primed cells to the body. The clinical relevance of these approaches has already been demonstrated for solid tumors such as melanoma and prostate cancer. The central nervous system was previously thought to be immune privileged. However we know now that the immune system is highly active in the brain and interacts with brain tumors. Thus, harnessing and exploiting this interaction represents an important approach for treating malignant brain tumors. We present a summary of progress in this area, focusing particularly on immune checkpoint inhibition, vaccines and T cell engineering.